“CERDIK” Healthy Lifestyle for Reducing Complications of Diabetes Mellitus - Dewiyuliana Dewiyuliana; Afni Yan Syah (Interest : Jurnal Ilmu Kesehatan, 2022)
Background: Diabetes mellitus that is not handled properly raises severe complications such as heart attack, stroke, infection of heavy legs or ulcers, kidney failure, sexual dysfunction, and eye disorders. The government recommends adopting healthy living behaviors with regular health checks, getting rid of cigarette smoke, diligent physical activity, a healthy and balanced diet, adequate rest, and stress management (CERDIK) to prevent and control diabetes complications. Methods: The population in this study were people with diabetes mellitus and the sample consisted of 32 respondents who were selected by purposive sampling with inclusion criteria. The CERDIK implementation is given once a week for one month. The risk of diabetes complications is calculated using the FINRISC Instrument (Fennish Diabetes Risk Score). Hypothesis Testing using the Paired Sample Test. Results: The results of this study show the majority of the females, reaching 75% with the most dominant age <45 years, 53.1%. The normal dominant waist circumference was 62.5%, the history of hypertension reached 56.2%, and increased blood sugar reached 59.4%. Most of the BMI was normal (81.3%), had a family history of DM (71.9%), 81.2% ate fruits and vegetables, and did 87.5% of physical activity. DM complications are effectively reduced with CERDIK (ρ=0.000). Conclusion: The risk of complications of diabetes mellitus can be prevented through a healthy lifestyle by routinely and regularly conducting regular health checks, avoiding and not smoking, being diligent and regular in exercising, consuming healthy foods with balanced calories, adequate rest, and being able to maintain a healthy lifestyle while managing stress.